The Performance of Secretariat DPRD to Appreciation the Implementation of function DPRD North Sulawesi Provincie. - Sahala, Jecica Nansi; Dengo, Salmin; Londa, Verry (Sam Ratulangi University, 2015)
ABSTRACT Parliament Secretariat is device area that has the task of providing administrative serv ices to the Parliament, so that the performance of the secretariat of the council will also determine the success of the implementation of Council functions. This research is to answer the question